Sp1 transcription factor is a modulator of estradiol leptin induction in placental cells. (September 2017) - Schanton, Malena; Maymó, Julieta; Pérez-Pérez, Antonio; Gambino, Yésica; Maskin, Bernardo; Dueñas, José Luis; Sánchez-Margalet, Víctor; Varone, Cecilia
Abstract: Introduction: Pleiotropic effects of leptin have been identified in reproduction and pregnancy, particularly in the placenta, where it functions as an autocrine hormone. The synthesis of leptin in normal trophoblastic cells is regulated by different endogenous biochemical agents, but the regulation of placental leptin expression is still poorly understood. We have previously reported that 17β-estradiol up-regulates placental leptin expression through genomic and nongenomic mechanisms. Methods: To improve the understanding of estrogen receptor mechanisms in regulating leptin gene expression, we examined Sp1 transcription factor effect on estradiol leptin induction in human BeWo cell line. Results: We demonstrated that Sp1 induces leptin expression determined by q RT-PCR, Western blot and transient transfection experiments. We also found that estradiol induction effect on leptin expression is enhanced by the over expression of Sp1 factor. Moreover, estradiol effect was not evidenced when Sp1 binding site on leptin promoter is mutated, suggesting that estradiol action is dependent on Sp1. On the other hand we showed data that demonstrate that Sp1 induction of leptin expression is insensitive to the antiestrogen ICI 182 780. By over expression experiments, we have also found that Sp1 effect on leptin expression could be mediated by estrogen receptor alpha. Supporting this idea, the downregulation of estrogen receptor alpha level through a specific siRNA, abolished Sp1 effect on leptin expression. Discussion: Taken together all these evidences suggest a cooperative behavior between estrogen receptor alpha and Sp1 transcription factors to induce leptin transcription. Highlights: Analysis of leptin expression by Sp1 transcription factor. Sp1 modulates estradiol induced leptin expression. Implication of Sp1 and ERalpha receptor in leptin expression.